Exploring the Potential Relationship Between Global Greenness and DALY Loss Due to Depressive Disorders - Asri, Aji Kusumaning; Tsai, Hui-Ju; Pan, Wen-Chi; Guo, Yue Leon; Yu, Chia-Pin; Wu, Chi-Shin; Su, Huey-Jen; Lung, Shih-Chun Candice; Wu, Chih-Da; Spengler, John D. (Frontiers in Psychiatry, 2022)
Objective: Prior studies have shown that greenness can reduce the burden of depressive disorders. However, most were focused on local-scale analyses while limited evaluated globally. We aimed to investigate the association between greenness and the burden of depressive disorders using data from 183 countries worldwide. Methods: We used the normalized difference vegetation index (NDVI) to estimate greenness. Country-level disability-adjusted life year (DALY) loss due to depressive disorders was used to represent depressive disorder burdens. A generalized linear mixed model was applied to assess the relationship between greenness and depressive disorders after controlling for covariates. Stratified analyses were conducted to determine the effects of greenness across several socio-demographic levels. Results: The findings showed a significant negative association between greenness and the health burden of depressive disorders with a coefficient of -0.196 (95% CI: -0.356, -0.035) in the DALY changes per interquartile unit increment of NDVI. The stratified analyses suggested beneficial effects of greenness on depressive disorders across sex, and various age groups especially for those aged <49 years, with low income, and/or those living in highly urbanized countries. Conclusions: Our study noted that greenness exposure was a significant negative association with the burden of depressive disorders. The findings should be viewed as recommendations for relevant authorities in supporting environmental greenness enhancement to reduce the mental burdens.